Batik Originality Marker As a Protection Model To The Manufacturer And Batik's Consumer - Eko Budi Susanto (Politeknik Negeri Semarang, 2018)
Such way from Pekalongan City Government in protecting the existence of crafstmen/batik seller and its consumer is by publishing region regulation of Pekalongan City Number 6 in year 2014. By that regulation, Pekalongan city government obligue all manufacturer/batik seller that produce and sell batik product in/from Pekalongan city should label their product with “ Batik Pekalongan”, hence it is not only functioned as a marker for consumer that is not able to identify the kinds of batik nor differentiate with printing batik, but also functioned as a protection model for the manufacturer/batik seller in Pekalongan. Nevertheless the absence of monitoring in the usage of label “Batik Pekalongan”, has been absorbed by certain manufacturer/batik seller to make fraud, thus the effort of Pekalongan city governmnt in giving protection to the manufacturer/batik seller and also their consumer hasn’t been well realized. The research resulted an e-label batik application that supports the effort of Pekalongan city government, by augmented reality technology utilization will make the label of “Batik Pekalongan” displaying such information about the kinds of batik, batik pattern/motif, the profile of the manufacturer/batik seller and other related information, if consumer scans that label by their smartphone, the information will be just displayed, and when the Pekalongan city government as the observer of the usage of batik label has done the validation based on the sustainability of the label certainty with the kinds of batik sold by the manufacturer/seller, the label of “Batik Pekalongan” will be functioned as the trusted mark